Inność, którą trzeba chronić. O empatii zbudowanej na dystansie - Winiecka, Elżbieta (Poznańskie Studia Polonistyczne. Seria Literacka, 2010)
The article is a review of Krystyna Pietrych’s book Co poezji po bolu. Empatyczne przestrzenie lektury (Łodż 2009) [What good pain and suffering bring in poetry. Emphatic dimensions of reading]. Since the reviewed book presents a bold and, to a large extent, novel approach to personalistic reading — based on a subjective, compassionate experience of an encounter with uncognizable and unreductible otherness of tormented man-poet, the reviewer focuses on the issues viewed as the most important for the method of emphatic reading adopted by the author. E. Winiecka analyses aesthetical and epistemological, as well as axiological possibilities and risks that emphatic criticism opens up for reexamination. Formulates her own opinion on the analytical method used by K. Pietrych in examining poetry, which is a recording of one’s mind in agony and suffering experienced by seven authors: Aleksander Wat, Zbigniew Herbert, Miron Białszewski, Stanisłw Barańzak, Janusz Szuber, as well as Julian Przybośand Anna Swirszczyńka. Outlines the methodological perspectives of the discussed work that traces the stages in the formation of literary depiction and representation of suffering. The text is also an attempt at defining and indicating the cognitive perspectives of emphatic criticism.